TECHNOLOGICAL STUDY OF ‘CORD’ IMPRESSIONS ON MIDDLE AND LATE ENEOLITHIC POTTERY IN UKRAINE - Burdo, Natalia B.; Kotova, Nadezhda S.; Videiko, Mykhailo Y. (Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Prahistorii, Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Wschodni, 2010)
The issues outlined in the above volume of Baltic-Pontic Studies (BPS) presented here, can be said to generate several important and complex questions among which, one relating to the topogenesis of ’corded’ ornamentation on the bio-cultural borderlands of east and west Europe, gave birth to an innovative research project. In this respect, specialist researchers of the Pontic-Baltic Eneolithic (from Middle and Late Neolithic contexts) chose 45 vessels (mostly fragments) originating from the Dnieper-Southern Bug drainage area and Vistula, dated to the 5th - 4th/3rd mill. BC for the purposes of microscopic analyses conducted with the aim of identifying ’corded’ patterns of ornamentation. These laboratory tests were led by an archaeologist specialising in microscopic analysis to identify interdisciplinary, pre-historic and archaic techniques in the textile crafts. The implications of the above tests would seem to warrant a manifold approach to possible conclusions on the basis of specialist (microscopic) criteria of differentiated - previously identified as macroscopic - in general terms as ’corded’ motifs of ceramic ware ornamentation (part 1). This also concerns an outline of investigation drawn from hermeneutics, prompted by various contexts such as historical and cultural assessment of bio-cultural communities and related findings as well as attempts to generate a coherent framework of linguistic and cultural research for ’corded ornamentation on ceramic ware’ (part 2). In discussing further the ’main issues’ presented in this publication of BPS 15 in respect to the hand manufacture of ceramic ware of the Vistula and Dnieper interfluvial region and its peoples, a modus operandi of investigation in the context of region has been proposed whereby researchers of this particular project have been given a free hand, as it were, in respect to the degree and forms of application in microscopic analyses and their findings. A series of commentaries has therefore arisen, from various points of view in so far as reflections on research conducted - possible future strategies for vital questions in this matter that are yet to be answered (part 3). It is assumed therefore that this volume has in some measure initiated a process of the highest consequence, one introducing a new level of off-site investigation into the genesis of corded ornamentation development, which deserves to be supported in addition through a personal engagement in this research field.